Recent mitigation strategies in engineered healthcare materials towards antimicrobial applications. (June 2022) - Vijayan, Vineeth M.; Walker, Melissa; Morris, J. Jeff; Thomas, Vinoy
Abstract: The design of material surfaces with antimicrobial properties is highly relevant to the fabrication of medical devices. Biofilm formation with its subsequent infection constitutes a primary reason for device failure. Hence, it is highly relevant to design healthcare materials with antibacterial properties which can efficiently resist biofilm formation and infection. The present current opinion article attempts to give a brief overview of some more recent advances in infection mitigation strategies. A major emphasis has been placed on material science and biological perspectives of biomaterial infection and corresponding mitigation strategies to prevent infection.